2008
DOI: 10.1007/s00531-008-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

The middle to late Miocene climatic development of Southwest Africa derived from the sedimentological record of ODP Site 1085A

Abstract: Sediments from the ODP Site 1085A were studied to investigate the impacts of global cooling in the Middle and Late Miocene on the climate in Southwestern Africa. The size composition of the sediment was analysed emphasising the silt fraction. A comparison with the modern grain size distribution and suitable transport processes made it possible to assign specific transport processes to the grain size composition. Three processes are considered for transport of terrigeneous silt: while there was no evidence foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In the eastern Pacific, nearly 50% of the diatom assemblages were replaced by cold‐water species during a major middle Miocene cooling from 14.9 to 12.4 Ma, reflecting increased upwelling and cooling of surface waters [ Barron and Baldauf , 1990]. Increased Antarctic glaciations promoting intermediate and bottom water formation [ Diekmann et al , 2003] and intensification of the Hadley circulation [ Flohn , 1978], combined with an intensified Southern Hemisphere southeast wind system [ Roters and Henrich , 2010], are inferred causes. Both mechanisms intensified upwelling at the west coasts of the Southern Hemisphere continents.…”
Section: Discussionmentioning
confidence: 99%
“…In the eastern Pacific, nearly 50% of the diatom assemblages were replaced by cold‐water species during a major middle Miocene cooling from 14.9 to 12.4 Ma, reflecting increased upwelling and cooling of surface waters [ Barron and Baldauf , 1990]. Increased Antarctic glaciations promoting intermediate and bottom water formation [ Diekmann et al , 2003] and intensification of the Hadley circulation [ Flohn , 1978], combined with an intensified Southern Hemisphere southeast wind system [ Roters and Henrich , 2010], are inferred causes. Both mechanisms intensified upwelling at the west coasts of the Southern Hemisphere continents.…”
Section: Discussionmentioning
confidence: 99%
“…The time interval of 11.8–11.4 Ma ago has been delineated as the Antarctic glaciation period Mi5 [ Miller et al , 1991; Westerhold et al , 2005]. The enhanced cooling during this time could have led to an increase in wind strength [ Roters and Henrich , 2010] and, subsequently, to an upwelling pulse. After 11.4 Ma, productivity tends to decrease, as reflected by a decrease in dinoflagellate cyst accumulation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our suggestion of enhanced input of terrigenous material at 11.3 and 11.2 Ma is supported by the study of Kastanja et al [2006], who found high values of terrigenous input at about 11.3 Ma. There is strong evidence that the Namib Desert was not fully developed and that most terrestrial material was transported into the research area via the Orange River [ Diekmann et al , 2003; Partridge , 1993; Roters and Henrich , 2010; Siesser , 1980]. The increase in nutrient availability in the upper water might therefore be the result of enhanced fluvial input during that time.…”
Section: Discussionmentioning
confidence: 99%
“…In southern Africa, progressive aridification of the climate began in the mid-Miocene (10-15 Ma), associated with the establishment of the Benguela upwelling system (Zachos et al, 2001;Cowling et al, 2009;Dupont et al, 2011). Approximately 10 Ma, the seasonal summer-dry climatic regime found in the present day in the CFR was established (Krammer et al, 2006;Roters & Henrich, 2010). The progressive aridification and the opening of new niches in the CFR in the last 10 million years (Myr) have been hypothesized to have triggered rapid speciation in several CFR clades (Verboom et al, 2009).…”
Section: Geomorphic and Climatic Historymentioning
confidence: 99%